2019
DOI: 10.4088/jcp.18r12527
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Anxiety Disorders During Pregnancy and the Postpartum Period

Abstract: Objective-To estimate the prevalence of anxiety disorders in pregnant and postpartum women and identify predictors accounting for variability across estimates. Data Sources-An electronic search of PsycINFO and PubMed was conducted from inception until July 2016, without date or language restrictions, and supplemented by articles referenced in the obtained sources. A Boolean search phrase utilized a combination of keywords related to pregnancy, postpartum, prevalence, and specific anxiety disorders.Study Select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
214
3
19

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 363 publications
(242 citation statements)
references
References 109 publications
6
214
3
19
Order By: Relevance
“…The average number of disorders measured by a given study was 3.4; Figure depicts the percentage of participants diagnosed with at least one disorder as a function of the number of disorders measured. These studies represent a partial sample from a meta‐analysis of AD within peripartum populations (Fawcett, Fairbrother, Cox, White, & Fawcett, ). A partial sample was selected for illustration purposes as it allowed us to focus on the methodology itself rather than becoming lost in the details of the included articles; for this reason, it is important that the present analyses be used for demonstration purposes only.…”
Section: Resultsmentioning
confidence: 99%
“…The average number of disorders measured by a given study was 3.4; Figure depicts the percentage of participants diagnosed with at least one disorder as a function of the number of disorders measured. These studies represent a partial sample from a meta‐analysis of AD within peripartum populations (Fawcett, Fairbrother, Cox, White, & Fawcett, ). A partial sample was selected for illustration purposes as it allowed us to focus on the methodology itself rather than becoming lost in the details of the included articles; for this reason, it is important that the present analyses be used for demonstration purposes only.…”
Section: Resultsmentioning
confidence: 99%
“…Recent systematic reviews report a pre‐valence of 15‐20% for antenatal and 10% for postnatal anxiety disorders 21,22 , with higher rates in LMIC versus HIC settings. Self‐reported anxiety symptoms are very common, and increase across the trimesters of pregnancy (with a mean prevalence of 25% in the third trimester) 21 .…”
Section: Prevalence Of Mental Disorders In the Perinatal Periodmentioning
confidence: 99%
“…Recently, a meta-analysis published in 2019 showed that antenatal anxiety disorders affect 20.7% of pregnant women; Confidence Interval CI [16.7%–25.4%]. Fawcett et al. (2019) reported generalized anxiety disorder (GAD) to be one of the most prevalent perinatal disorders during pregnancy; other types of antenatal anxiety disorders were described, such as panic attacks, obsessive-compulsive disorder, acute stress disorder, specific phobia, and post-traumatic stress disorder.…”
Section: Introductionmentioning
confidence: 99%